Syarat Objektifitas Dan Subjektifitas Penangguhan Penahanan - Padian Adi; Ismail Koto (Universitas Muhammadiyah Sumatera Utara, 2019)
Requests for suspension of detention can be granted with conditions that must be met. The requirements that must be met by the applicant for detention suspension are 2 (two) conditions, namely subjective conditions and objective conditions. The subjective condition referred to is the existence of subjective judgments made by the investigator or public prosecutor or judge to assess the reason for the applicant's suspension of detention granted or rejected. Whereas the objective requirement is that there is a guarantee in accordance with Article 31 of the Criminal Procedure Code which states that an authorized official at the examiner's level can suspend detention. This writing uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The procedure of data collection is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online, which are then analyzed through the content analysis method (centent analysis method) with a focus on the problem of how objective conditions are and the subjectivity of detention suspension in the Criminal Procedure Code (KUHAP) in Indonesia. From the results of the study it is known that the objective and subjective conditions of suspension of detention in Indonesia are suspects must fulfill the conditions specified in the explanation of Article 31 of the Criminal Procedure Code (KUHAP), which is the requirement for reporting, not leaving the house and / or not leaving town the terms of subjectivity include consideration of institutional officials asking for money guarantees and / or guarantees of people. Consideration of objectivity, namely the suspect is not worried about escaping, damaging or removing evidence and will repeat the action. Consideration of subjectivity, namely the suspect is willing to sign and fulfill the terms of detention suspension